2016
DOI: 10.1007/s10459-016-9677-6
|View full text |Cite
|
Sign up to set email alerts
|

The validity of student tutors’ judgments in early detection of struggling in medical school. A prospective cohort study

Abstract: Early identification and support of strugglers in medical education is generally recommended in the research literature, though very little evidence of the diagnostic qualities of early teacher judgments in medical education currently exists. The aim of this study was to examine the validity of early diagnosis of struggling in medical school based on informal teacher judgements of in-class behavior. The study design was a prospective cohort study and the outcomes/truth criteria were anatomy failure and medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Interviews ( n = 2) and practical demonstrations of teaching skills ( n = 2) were the most commonly used selection tools, followed by reflective essays ( n = 1) and research proposals ( n = 1). Anatomical knowledge and/or academic merit was the most commonly cited selection criterion ( n = 6), with several studies indicating a preference for high‐performing near‐peer students (Durán et al, ; Erie et al, ; Lachman et al, ; Reyes‐Hernández et al, ; O'Neill et al, ). Enthusiasm for teaching was another key selection criterion ( n = 3) with one study stating that teachers were selected purely based on their “enthusiasm and willingness to teach” rather than their anatomical knowledge (Stephens et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Interviews ( n = 2) and practical demonstrations of teaching skills ( n = 2) were the most commonly used selection tools, followed by reflective essays ( n = 1) and research proposals ( n = 1). Anatomical knowledge and/or academic merit was the most commonly cited selection criterion ( n = 6), with several studies indicating a preference for high‐performing near‐peer students (Durán et al, ; Erie et al, ; Lachman et al, ; Reyes‐Hernández et al, ; O'Neill et al, ). Enthusiasm for teaching was another key selection criterion ( n = 3) with one study stating that teachers were selected purely based on their “enthusiasm and willingness to teach” rather than their anatomical knowledge (Stephens et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The fact that an aggregate score of student participation in class collected systematically in a simple scale by multiple teachers can be useful in the process of identifying potential dropouts is, to our best knowledge, an original contribution. Prior studies had already shown the potential of using tutors' information to identify struggling students (Wijnia et al 2014;O'Neill et al 2016;Wijnia et al 2016), but in these studies the tutor/ students ratio was low and, therefore, there were more frequent contacts with the students. Our study provides other contextual circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Struggling might also be indicative of future lapses in professional behavior as a doctor, as suggested by retrospective studies in the USA and the UK (Papadakis et al 2004;Yates and James 2010). Signs of struggling identified by O'Neill et al (2016) include issues with participation (e.g. passivity, lack of initiative, lack of active participation in the classroom), commitment (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If a student is struggling with material or not using effective study habits, the student can quickly fall behind to the point where they simply cannot be successful in the course. Instructor identification of struggling students can potentially be used to try to prevent this from occurring (O'Neill et al 2016). As a proactive approach, we use an informal in-class assessment in our scheduled lab periods to gauge student learning.…”
Section: Informal In-class Assessmentmentioning
confidence: 99%